Communal and agentic behaviour in response to facial emotion expressions. (19th March 2013) - aan het Rot, Marije; Hogenelst, Koen; Gesing, Christina M.
<x xml:space="preserve">Abstract</x> Facial emotions are important for human communication. Unfortunately, traditional facial emotion recognition tasks do not inform about how respondents might behave towards others expressing certain emotions. Approach‐avoidance tasks do measure behaviour, but only on one dimension. In this study 81 participants completed a novel Facial Emotion Response Task. Images displaying individuals with emotional expressions were presented in random order. Participants simultaneously indicated how communal (quarrelsome vs. agreeable) and how agentic (dominant vs. submissive) they would be in response to each expression. We found that participants responded differently to happy, angry, fearful, and sad expressions in terms of both dimensions of behaviour. Higher levels of negative affect were associated with less agreeable responses specifically towards happy and sad expressions. The Facial Emotion Response Task might complement existing facial emotion recognition and approach‐avoidance tasks.